Matematyka

Autorzy:Ewa Duvnjak, Ewa Kokiernak-Jurkiewicz

Wydawnictwo:WSiP

Rok wydania:2015

Oblicz (-7)^2+(-1)^2 4.67 gwiazdek na podstawie 6 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

`a)\ (-7)^2+(-1)^2=(-7)*(-7)+(-1)*(-1)=49+1=50`

`b)\ (-6-4)^2-2^2=(-10)^2-2*2=(-10)*(-10)-4=100-4=96`

`c)\ (-8)^2-(-3)^3=(-8)*(-8)-(-3)*(-3)*(-3)=64+27=91`

`d) \ (6-10+12)^2-(-4+5)^3=8^2-1^3=8*8-1*1*1=64-1=63`

`e)\ (-1/2)^2-(4/5)^0=(-1/2)*(-1/2)-1=1/4-1=-3/4`

`f)\ (1 1/2)^3-(-1/2)^2=(3/2)^3-(-1/2)*(-1/2)=`

`\ \ \ =3/2*3/2*3/2-1/4=27/8-2/8=25/8=3 1/4`

`g)\ (-1,2)^2-(-1,44)^1=(-1,2)*(-1,2)-(-1,44)=1,44+1,44=2,88`

`h)\ (-0,1)^3+(-2,3)^2=(-0,1)*(-0,1)*(-0,1)+(-2,3)*(-2,3)=-0,001+5,29=5,289`